2007
DOI: 10.1177/0960327107087799
|View full text |Cite
|
Sign up to set email alerts
|

Two cases of valproic acid poisoning treated with l-carnitine

Abstract: Two cases of acute valproic acid poisoning with central nervous system depression and raised ammonia level without hepatotoxicity were reported. They were treated successfully with the use of the antidotes: l-carnitine and other supportive measures. Clinical manifestation and progress was described, and discussion is focused on the use of l-carnitine in valproic acid–induced hyperammonemia, from its mechanism to the clinical experiences in the literature. Based on the favorable response of our two cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 8 publications
0
14
0
Order By: Relevance
“…The typical features of VHE are acute onset of impaired consciousness, focal neurological symptoms, and increased seizure frequency, with an elevated ammonia level and normal liver function test 12 . The VPA‐induced hepatotoxicities are further classified into four subtypes: transient elevation of liver transaminases, reversible hyperammonemia, toxic hepatitis, and a Reye‐like syndrome 2 . An increase in transaminases did not occur in the present case but, due to the increase in PT, FFP was given.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…The typical features of VHE are acute onset of impaired consciousness, focal neurological symptoms, and increased seizure frequency, with an elevated ammonia level and normal liver function test 12 . The VPA‐induced hepatotoxicities are further classified into four subtypes: transient elevation of liver transaminases, reversible hyperammonemia, toxic hepatitis, and a Reye‐like syndrome 2 . An increase in transaminases did not occur in the present case but, due to the increase in PT, FFP was given.…”
Section: Discussionmentioning
confidence: 68%
“…There is no specific antidote or guidelines for managing VPA intoxication. Hyperammonemia is also associated with VPA both in therapeutic and overdose situations and may contribute to the central nervous system (CNS) toxicity 2 …”
mentioning
confidence: 99%
“…Patients should have electrolytes and liver biochemistry checked and, in severe poisoning, ammonia and acid-base status need to be monitored. Intravenous carnitine administration has been reported to alleviate features of toxicity in some patients, and should be considered in patients with encephalopathy, severe hyperammoniaemia, and liver impairment 10 , 11. Extracorporeal techniques, for example the molecular adsorbent recirculating system (MARS), have been used to support poisoned patients with liver toxicity, but these have not been studied in the setting of valproate toxicity 12…”
Section: Discussionmentioning
confidence: 99%
“…Among others, the effects of L-carnitine and its derivates have been investigated in Alzheimer's disease, chronic fatigue syndrome, Parkinson's disease, and neuropathic pain, as well as in valproic acid intoxication associated with CNS depression and raised ammonia levels without hepatotoxicity (Beal, 2003;Chan et al, 2007;Kuratsune et al, 2002;Pittler 7 Ernst, 2008;Silva et al, 2008). Fatty acid metabolism plays a major role in brain energy metabolism since acetyl-CoA enters the mitochondrial TCA cycle via PDH in both astrocytes and neurons (Fig.…”
Section: Pharmaceutical Use Of L-carnitine In Brain Disordersmentioning
confidence: 99%
“…Valproic acid is a broad-spectrum antiepileptic drug which is known to reduce L-carnitine level, and can lead to HA. It has been suggested that L-carnitine may decrease ammonia levels by binding to valproic acid (Chan et al, 2007, Lheureux et al, 2005, Wadzinski et al, 2007.…”
Section: Pharmaceutical Use Of L-carnitine In Brain Disordersmentioning
confidence: 99%